Design of Learning Model of Logic and Algorithms Based on APOS Theory - Sulis Janu Hartati (International Journal of Evaluation and Research in Education (IJERE), 2014)
This research questions are ‘how do the characteristics of learning model of logic & algorithm according to APOS theory’ and ‘whether or not these learning model can improve students learning outcomes‘.This research was conducted by exploration, and quantitative approach. Exploration used in constructing theory about the characteristic of the learning model of logic and algorithms based on APOS theory. The hypothesis tested was did the mean value of class by using learning model based on APOS theory greater than other class. The results showed that characteristics of learning model used APOS theory had achievement map of competency be classified into four levels. They are action; process; object; and scheme. Action is ability to understand concept by using external stimulus. Process is ability to think about the same action based on specific input and output. Object is ability to think about transformation on action and process, so that they can associate between action and process, process and process itself based on a specific output. Scheme is ability to construct relationship of action, process, object, and other concept to solve the problem in making business document. It is proven that mean value is greater than the other. Especially in lesson plan of action and process.DOI: http://dx.doi.org/10.11591/ijere.v3i2.5743